Some Questions about the Basis of the Communication Theory of Law - Díaz de Terán Velasco, María Cruz (2017)
The present article turns on the basis of the Communication Theory of Law as it has been developed by Professor Gregorio Robles, who has elaborated his theory being based on the conception of Law as a system of communication between the human beings. This article focuses on analyzing one of the fundamental elements concerning his Theory: the idea of conceiving the Law as a text. The article finishes with a few valuations.